2023
DOI: 10.4250/jcvi.2022.0053
|View full text |Cite
|
Sign up to set email alerts
|

Role and Clinical Importance of Progressive Changes in Echocardiographic Parameters in Predicting Outcomes in Patients With Hypertrophic Cardiomyopathy

Abstract: BACKGROUND The prognostic utility of follow-up transthoracic echocardiography (FU-TTE) in patients with hypertrophic cardiomyopathy (HCM) is unclear, specifically in terms of whether changes in echocardiographic parameters in routine FU-TTE parameters are associated with cardiovascular outcomes. METHODS From 2010 to 2017, 162 patients with HCM were retrospectively enrolled in this study. Using echocardiography, HCM was diagnosed based on morphological criteria. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Diastolic dysfunction is a hallmark of HCM, and the clinical importance of LA enlargement and mechanical function, which are indicators of chronic LV diastolic dysfunction and thromboembolic risks, 19 , 20 , 21 , 22 is well known in patients with HCM. 9 , 10 , 11 , 12 , 23 While actively applying an implantable cardioverter defibrillator in patients at high risk of sudden cardiac death or performing septal myectomy in patients with symptomatic obstructive HCM, the residual risk in HCM patients is that of heart failure and stroke according to underlying LA and LV functions. 1 In addition, because interest in medical septal reduction therapy using cardiac myosin inhibitors has recently increased, 24 the effect of reducing LVOT obstruction on myocardial mechanics is expected to become an important issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diastolic dysfunction is a hallmark of HCM, and the clinical importance of LA enlargement and mechanical function, which are indicators of chronic LV diastolic dysfunction and thromboembolic risks, 19 , 20 , 21 , 22 is well known in patients with HCM. 9 , 10 , 11 , 12 , 23 While actively applying an implantable cardioverter defibrillator in patients at high risk of sudden cardiac death or performing septal myectomy in patients with symptomatic obstructive HCM, the residual risk in HCM patients is that of heart failure and stroke according to underlying LA and LV functions. 1 In addition, because interest in medical septal reduction therapy using cardiac myosin inhibitors has recently increased, 24 the effect of reducing LVOT obstruction on myocardial mechanics is expected to become an important issue.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of LV global longitudinal strain (GLS) in HCM is a significant prognostic factor of future clinical events such as sudden cardiac death, heart failure, and ventricular arrhythmia 5–8 . Left atrium (LA) size and function affected by progression of LV diastolic dysfunction also are prognostic factors in patients with HCM 9–12 . Therefore, studying LA and LV mechanical functional changes after septal myectomy would be clinically important to predict prognosis in patients with obstructive HCM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3) Other studies have suggested different parameters, such as changes in left atrial volume index (LAVI), to be clinically significant. 6) However, even with the abundance of longitudinal echocardiographic data for HCM patients, there is no consensus on the clinical meaning of changes in echocardiographic predictors (e.g., LVEF, left ventricular outflow tract obstruction, LAVI, E/e′, tricuspid regurgitation velocity, and maximum wall thickness) over a certain period. Thus, the authors of this study attempted to re-evaluate certain echocardiographic predictors and retrospectively scrutinize the changes in patient echocardiograms throughout the course of the disease to determine which echocardiographic parameters are clinically useful as predictors of poor cardiovascular outcomes.…”
mentioning
confidence: 99%